2014
DOI: 10.1016/j.aap.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

The role of experience and advanced training on performance in a motorcycle simulator

Abstract: Motorcyclists are over-represented in collision statistics. While many collisions may be the direct fault of another road user, a considerable number of fatalities and injuries are due to the actions of the rider. While increased riding experience may improve skills, advanced training courses may be required to evoke the safest riding behaviours. The current research assessed the impact of experience and advanced training on rider behaviour using a motorcycle simulator. Novice riders, experienced riders and ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Other HP tests have analysed the HP skills of motorcyclists without driving experience [28] and in Australia the HP of car drivers and motorcyclists has been compared [29]. HP tests were also designed from the perspective of motorists in the UK [30,31] and in other countries such as Italy [32,33]. Recently, HP from the perspective of professional drivers has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Other HP tests have analysed the HP skills of motorcyclists without driving experience [28] and in Australia the HP of car drivers and motorcyclists has been compared [29]. HP tests were also designed from the perspective of motorists in the UK [30,31] and in other countries such as Italy [32,33]. Recently, HP from the perspective of professional drivers has been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Without sustained action, road traffic crashes are predicted to become the seventh leading cause of death by 2030 [ 2 ] . Related literature has attested to the key role of safe driving in reducing the rate of driving-induced injuries, offenses and violations [ 3 ]. In the Iranian context, the foremost factor involved in the occurrence of car accidents is human factors [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the introduction of physical tilt in the roll axis did not lead to significant changes in rider behavior, nor did it add to the perceived realism of the simulator. This is in contrast with the idea that motorcycle tilt is an important contributor to the riding experience in a simulator (Cossalter et al, 2010;Crundall et al, 2014;Lobjois et al, 2016a).…”
Section: Effects Of Motorcycle Simulator Configuration On Steering Anmentioning
confidence: 78%
“…Lobjois et al (2016b) showed that the in-lane position adopted by motorcyclists was shifted towards the inner edge line with a standard deviation of 30 cm, suggesting that they negotiated bends by spending most of the time in the inside part of the lane. Crundall et al (2014) revealed a similar 'racing line' strategy. Investigating the effects of rider experience on steering strategies, Crundall et al (2012) showed that riders crossed the lane center before the apex of the bend, suggesting that they preferentially adopted a 'racing path'.…”
mentioning
confidence: 83%
See 1 more Smart Citation